Open Data Research in Spain Published via the Diamond Route: A Systematic Review - Curto-Rodríguez, Ricardo; Leal-Matilla, Alberto; Ferrández, Daniel; Marcos-Sánchez, Rafael (Publications, 2026)
In the information society, open data is an important resource for creating economic value. This study conducts a systematic review, following the PRISMA methodology, of articles published between 2000 and 2025 in Scopus and Web of Science that include the terms Open Data and Spain (in Spanish or English) in their title and/or abstract, with the aim of assessing how Law 37/2007 on the reuse of public sector information has influenced the publications analyzed. After identifying 240 articles in Scopus and 109 in Web of Science and applying the exclusion criteria, we observe that 37 studies use the Diamond Open-Access publishing route. The results are organized into four categories corresponding to the research questions, which represent a meaningful theoretical contribution and enhance current knowledge on open data research in Spain. The identification of obstacles to the effective use of open data—such as the lack of standardization, poor information quality, and the vague definition of reuse conditions—entails practical implications of significant value for managers of open data portals seeking to improve their initiatives.
Keywords: open data; Diamond Open-Access publications; Spain; systematic review